P368 PHYSICAL AND PSYCHOLOGICAL RECONDITIONING IN LONG COVID SYNDROME: RESULTS OF AN OUT–OF–HOSPITAL EXERCISED–BASED CARDIOVASCULAR REHABILITATION PROGRAM. (18th May 2022) - Compagno, S; Palermi, S; Pescatore, V; Brugin, E; Tegon, G; Sarto, M; Marin, R; Calzavara, V; Nizzetto, M; Scevola, M; Albertin, C; Biffi, A; et al.
Abstract: Background: Long Covid Syndrome (LCS) is used to describe signs and symptoms that continue or develop after acute COVID–19 infection. Natural history and treatments of this syndrome are still poorly understood, even if evidence suggests the potential role of physical rehabilitation in improving symptoms in these subjects. Aim: The aim of the present study was to evaluate safety, effectiveness and feasibility of a multidisciplinary, out–of–hospital, exercise–based cardiac rehabilitation (EBCR) program, of two months duration, in improving symptoms and physical and psychological parameters in patients with LCS Methods Thirty consecutive patients with LCS (18 males, mean age 58 years) underwent an accurate medical screening process including anthropometric and muscular strength evaluation, cardiopulmonary exercise test (CPET), quality of life (QoL) and psychological appraisal before and after an EBCR program. Results: At baseline, all LCS patients were strongly symptomatic and showed severe impairments in physical performance, QoL and psychological parameters. No adverse effects and dropouts were observed during the exercise training sessions. After the EBCR program, COVID–19 residual symptoms significantly decreased and significant improvements in upper and lower limb muscular strength, CPET parameters, perceived physical and mental health, depression and anxiety were observed. Conclusions: The present study confirms the severe physical and psychological impairment of patients with LCS and suggests that a multidisciplinary EBCR program could promote their physical and psychological recovery